2021
DOI: 10.1021/acs.energyfuels.0c03965
|View full text |Cite
|
Sign up to set email alerts
|

Gas Generation Potential and Characteristics of Oil-Prone Shale in the Saline Lacustrine Rifting Basins: A Case Study of the Dongpu Depression, Bohai Bay Basin

Abstract: In comparison to the continuous breakthrough in shale gas of marine basins, the pace of study of lacustrine basins is relatively slow. The latest studies have shown the saline lacustrine rifting basins (SLRBs) are one of the favorable exploration areas from the view of shale pore, mineral composition, and organic matter accumulation. However, the study on the gas generation potential and characteristics is still lacking because the traditional view is that lacustrine source rocks are oil-prone. Therefore, to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The oil content in shales is relatively low at the immature stage. Nevertheless, if the thermal maturity is too high, this leads to the so-called secondary cracking of oil into gas in shales, and oil is not effectively retained (Zhang P. Y. et al, 2021). Exploration practices of shale oil revealed that the Ro value in the shale oil palys broadly ranges from 0.5 to 1.6% (Cardott, 2012;.…”
Section: Restriction Of Organic Matter Properties On Oil Retentionmentioning
confidence: 99%
“…The oil content in shales is relatively low at the immature stage. Nevertheless, if the thermal maturity is too high, this leads to the so-called secondary cracking of oil into gas in shales, and oil is not effectively retained (Zhang P. Y. et al, 2021). Exploration practices of shale oil revealed that the Ro value in the shale oil palys broadly ranges from 0.5 to 1.6% (Cardott, 2012;.…”
Section: Restriction Of Organic Matter Properties On Oil Retentionmentioning
confidence: 99%
“…The second review by Zhang and Cheng is a mini review on the technical aspects of sample preparation and data analysis using small-angle neutron scattering (SANS) and ultrasmall-angle neutron scattering (USANS) for shale samples. The original research articles cover a wide spectrum of research on shale gas, including reservoir characteristics, ,,, reservoir modeling, ,,, exploration, equipment-related, ,, gas transport properties, ,,,, shale property characterization, , gas adsorption, ,, gas generation, produced water treatment, , methane conversion, etc.…”
Section: Shale Gasmentioning
confidence: 99%
“…There are three types of organic-rich shales in China: Early Paleozoic shales deposited in the marine facies system, Carboniferous to Permian shales formed in marine–continental transitional environments, and Cenozoic shales mainly deposited in the lacustrine facies system. Despite differences in their sedimentary environments, the three types of shales exhibit a significant presence of quartz. In marine shale deposits, silicon is considered a crucial nutrient for plankton growth and a vital element for organisms, which is often associated with surface primary productivity and water environmental history .…”
Section: Introductionmentioning
confidence: 99%